Taking the Elephants' Perspective: Remembering Elephant Behavior, Cognition and Ecology in Human-Elephant Conflict Mitigation - Mumby, Hannah S.; Plotnik, Joshua M. (Frontiers in Ecology and Evolution, 2018)
Conflict between humans and wildlife is an increasing problem worldwide due to human population growth and habitat fragmentation, with growing interest amongst scientists and conservationists in developing novel solutions towards sustainable coexistence. Current efforts to mitigate human-wildlife conflict, however, are often unbalanced; they consider immediate human-centric concerns and offer deterrents against wildlife, rather than offering solutions to the underlying problems. Recently, there has been an increase in the number of calls to action for the integration of animal behaviour, cognition and knowledge of individual variation into conservation practice. However, as elephant researchers, we have seen that most human-elephant conflict mitigation strategies employed in Asia and Africa are based on conditioning fear in elephants, or general monitoring of individual or group activities aimed at altering elephant movements, rather than understanding and providing for elephant and human needs. We see an opportunity to do more by investigating elephant behaviour, cognition and ecology at the level of the individual to prevent conflict from occurring in the first place. Here, we review studies on elephants to illustrate this concept and to outline avenues for the application of research on elephant ecology, life history, behaviour and personality to the development of new, comprehensive conservation strategies that take both human and elephant behaviour into account.